2021
DOI: 10.34001/nuiej.v1i1.56
|View full text |Cite
|
Sign up to set email alerts
|

Digital Islamic Financial Literacy and Inclusion on Profitability of Micro, Small and Medium Enterprises

Abstract: Digital Islamic financial literacy and inclusion are the main factors in playing a role in increasing the profitability of Microfinance Microfinance Enterprises (MSMEs). This study uses a quantitative approach, data collection techniques using questionnaires, and the data source of this research is the owners of MSMEs in Bantul. Based on the results of this study, it is stated that digital Islamic financial literacy has a positive and significant effect on the profitability of MSMEs in Bantul, while digital Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…The study found that financial information literacy significantly impacts agribusiness performance sustainability among entrepreneurs. In addition, the proposed link between financial information literacy and strategic decision-making effectiveness among agribusiness entrepreneurs was confirmed (Pranatasari et al, 2022). It is concluded that financial information literacy is crucial for agribusiness entrepreneurs to make strategic decisions and improve their performance sustainability.…”
Section: B Financial Literacy and Profitability Of Agribusinessmentioning
confidence: 75%
See 1 more Smart Citation
“…The study found that financial information literacy significantly impacts agribusiness performance sustainability among entrepreneurs. In addition, the proposed link between financial information literacy and strategic decision-making effectiveness among agribusiness entrepreneurs was confirmed (Pranatasari et al, 2022). It is concluded that financial information literacy is crucial for agribusiness entrepreneurs to make strategic decisions and improve their performance sustainability.…”
Section: B Financial Literacy and Profitability Of Agribusinessmentioning
confidence: 75%
“…Farmers, managers, and industry experts with higher levels of financial literacy demonstrate better capabilities in managing cash flows, allocating resources, and assessing investment opportunities, thereby optimizing financial performance and minimizing risks (Obi-Anike et al, 2023;Rahmansyah et al, 2023). Moreover, financial literacy empowers agribusinesses to access financial markets, secure funding, and negotiate favorable terms, enhancing their financial resilience and flexibility in the face of market uncertainties and economic challenges (Pranatasari et al, 2022).…”
Section: Influence Of Financial Literacy On Profitability Of Agribusi...mentioning
confidence: 99%
“…Islamic financial literacy has a significant positive impact on the financial management of MSMEs (Pranatasari et al, 2021). Some positive impacts include more effective financial management, diversification of financing sources, increased trust and reputation, and access to Islamic financial markets (Suwarsi et al, 2022).…”
Section: The Importance Of Sharia Financial Literacy For Msme Playersmentioning
confidence: 99%
“…These principles include the prohibition of riba (usury), fairness in transactions, and a prohibition against investment in businesses that are incompatible with Islamic values such as alcohol and gambling. In the context of a sharia-based economy, MSMEs that understand sharia financial literacy will be better able to follow these principles in their operations, which in turn can increase customer trust and access to wider markets [2].…”
Section: Introductionmentioning
confidence: 99%